THE APPLICATION OF KAHOOT! TO IMPROVE CLASSROOM DYNAMICS AND LEARNING PROCESS IN ENGLISH STRUCTURE CLASS - Thea Marisca Marbun; Harpain Harpain (LINGUISTIKA, 2016)
There were problems that the researcher found in the teaching and learning process of English Structure class of Bandar Lampung University related to the learners’ assumption, method, and medium used. Based on the problems found in English Structure class of Bandar Lampung University, the writer chose the media using Kahoot! as a solution.  Kahoot! is one of techniques that can can be applied to the learners which is expected to affect the classroom dynamics and facilitate the learning process. The objectives of this research are to know how aplication of kahoot! Affect classroom dynamics and facilitating learning prices. The research method used in this research was classroom action research. One of the functions of classroom action research is to find the learners’ main problem and give solution for the problem. The research was carried out in two cycles. Every cycle include plan, action, observation, and reflection. The data of the research were qualitative. The qualitative data obtained by observing the teaching and learning process and interviewing the learners of Structure I class. The data were also obtained by giving questionnaire to support the data. Based on the observation in the classroom and interview the learners, they showed a great enthusiasm even though some problems appeared because of the capacity of internet connection. When observation was carried out, the learners enjoyed their activities using Kahoot! in the classroom. The atmosphere in the classroom was positive where they felt comfortable and relaxed to communicate with other learners and also with the researcher. It also can be seen from the result of the questionnaire.  The result of the research showed that the application of Kahoot! affected the classroom dynamics and facilitated the learning process in the teaching and learning activity. The researcher also expects that Kahoot! can assist English teacher in preparing interesting learning material and making it as alternative in creative learning.